2020
DOI: 10.1080/17441692.2020.1839932
|View full text |Cite
|
Sign up to set email alerts
|

‘It has become everybody’s business and nobody’s business’: Policy actor perspectives on the implementation of TB infection prevention and control (IPC) policies in South African public sector primary care health facilities

Abstract: South Africa is increasingly offering screening, diagnosis and treatment of tuberculosis (TB), and especially drug-resistant TB, at the primary care level. Nosocomial transmission of TB within primary health facilities is a growing concern in South Africa, and globally. We explore here how TB infection prevention and control (IPC) policies, historically focused on hospitals, are being implemented within primary care facilities. We spoke to 15 policy actors using in-depth interviews about barriers to effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…, 2020 ). Umoya omuhle collected a wealth of information on the policies, norms and values governing TB-IPC processes for clinic staff and patients, as well as on the infrastructure and resources for TB-IPC, implementation challenges, and on existing levels of indoor ventilation and congregation to parametrize a model of Mtb transmission in the clinics and surrounding communities ( Colvin et al. , 2020 ; Mccreesh et al.…”
Section: Methodsmentioning
confidence: 99%
“…, 2020 ). Umoya omuhle collected a wealth of information on the policies, norms and values governing TB-IPC processes for clinic staff and patients, as well as on the infrastructure and resources for TB-IPC, implementation challenges, and on existing levels of indoor ventilation and congregation to parametrize a model of Mtb transmission in the clinics and surrounding communities ( Colvin et al. , 2020 ; Mccreesh et al.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have usefully explored the relationships between aspects of organisational culture, such as leadership, and coordinated change efforts in health facilities and improved implementation of IPC [20,34]. Our participants, along with those in other studies [15,31] have likewise recognised that changes in mask use by opinion leaders within the clinic context could help to create a local cultural norm of mask-wearing.…”
Section: Discussionmentioning
confidence: 90%
“…In the context of the high TB burden in South Africa, it is not surprising that the risk of TB infection has become 'normalised'. Research on the development of TB-IPC policy in South Africa has described how the pervasiveness of TB triggers a sense of "fatalism" or "toughness" in HCWs and for those who have worked in the field for a long time, a sense of "invulnerability to infection" [31]. This sense of pervasiveness and inevitability can also make TB risk less visible and feel less urgent.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy may be due to a small hospital sample size in this study. TBIPC is an important component in overall TB control efforts within health facilities [ 9 , 42 ]. Our study demonstrated that the use of natural ventilation was variable between the different facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of TB transmission amongst health workers is also influenced by the patient population, type of occupation, regional TB prevalence, medical facility access [ 4 , 38 ], inadequate infrastructure, poor ventilation [ 39 , 40 ], delayed and incorrect diagnosis [ 41 ], and TB infection control programmes’ efficacy [ 4 , 38 , 40 ]. The resource allocation shift to the COVID-19 pandemic also poses a serious threat to the reduction of the global TB detection and notifications, thereby hampering the progress made in recent years [ 42 , 43 , 44 ]. Between January and June 2020, SA was among the four countries that reported a significant decrease in the number of TB-diagnosed people that account for 44% of global TB cases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%